Promoting compliance with the rules regulating humanitarian relief operations in armed conflict: some challenges - Akande, D; Gillard, E (Cambridge University Press, 2017)
In recent years, the increasingly frequent and, in certain contexts, extremely severe, impediments to the provision of humanitarian assistance to civilians in need have focused attention on how to enhance compliance with the rules of international humanitarian law (IHL) regulating humanitarian relief operations. Efforts to hold accountable parties to armed conflict and persons responsible for unlawfully impeding humanitarian relief operations face the challenge that the underlying rules give parties latitude as to how to implement the central obligation to allow and facilitate rapid and unimpeded passage of humanitarian supplies, equipment and personnel. The present article outlines the rules of IHL regulating humanitarian relief operations and highlights the difficulties in determining, in the majority of situations, whether they have been violated. It then presents current endeavours to promote accountability. It concludes with some reflections on whether the threat of accountability is the most effective way of enhancing compliance with this area of IHL, at least while efforts are underway to negotiate access.